2014
DOI: 10.1186/1741-7015-12-33
|View full text |Cite
|
Sign up to set email alerts
|

Early life programming as a target for prevention of child and adolescent mental disorders

Abstract: This paper concerns future policy development and programs of research for the prevention of mental disorders based on research emerging from fetal and early life programming. The current review offers an overview of findings on pregnancy exposures such as maternal mental health, lifestyle factors, and potential teratogenic and neurotoxic exposures on child outcomes. Outcomes of interest are common child and adolescent mental disorders including hyperactive, behavioral and emotional disorders. This literature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
110
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 123 publications
(119 citation statements)
references
References 169 publications
4
110
0
3
Order By: Relevance
“…This is in line with previous human and animal studies demonstrating that adverse early life experiences such as being exposed as a fetus to maternal stress, is related to the development of health and behavioural problems later in life [4][5][6][7][8][9]. However, the specific underlying mechanism for the association between prenatal stress exposure and dyspnoea perception in adulthood observed in the present study remains unclear.…”
supporting
confidence: 52%
See 3 more Smart Citations
“…This is in line with previous human and animal studies demonstrating that adverse early life experiences such as being exposed as a fetus to maternal stress, is related to the development of health and behavioural problems later in life [4][5][6][7][8][9]. However, the specific underlying mechanism for the association between prenatal stress exposure and dyspnoea perception in adulthood observed in the present study remains unclear.…”
supporting
confidence: 52%
“…Similarly, potential factors related to pregnancy [5,7] such as duration of pregnancy, birthweight and maternal consumption of cigarette smoke, caffeine and alcohol during pregnancy were not related to the present findings. Therefore, future studies are required to test further potential mechanisms that might underlie the observed association between early life adversity and perception of dyspnoea later in life.…”
mentioning
confidence: 42%
See 2 more Smart Citations
“…greater probability of females being exposed to various stressors which predisposes them to depression) (48). There are also studies showing that female adolescents in western populations are more vulnerable to the quality of their relationship to their parents, than males (5) that early stress exposure may have a long terms impact on child and adolescent depression (49,50), that there may be differences emerging due to the use of emerging technologies such as social media (51).…”
Section: Gender and Age Differencesmentioning
confidence: 99%